Histone acetyltransferase inhibition reverses opacity in rat galactose-induced cataract. - Masaya Nagaya; Risa Yamaoka; Fumito Kanada; Tamotsu Sawa; Masaru Takashima; Yoshihiro Takamura; Masaru Inatani; Masaya Oki (PLoS ONE)
Cataract, a disease that causes opacity of the lens, is the leading cause of blindness worldwide. Cataracts secondary to diabetes are common, even in young patients, so they are of significant clinical importance. Here, we used an ex vivo model of galactose-induced cataracts in the rat lens to investigate the therapeutic effects of histone acetyltransferase (HAT) inhibitors. Among the tested HAT inhibitors, TH1834 was the only one that could reverse most of the opacity once it had formed in the lens. Combination treatment with C646/CPTH2 and CBP30/CPTH2 also had therapeutic effects. In lens cross-sections, vacuoles were present in the tissue of the cortical equatorial region of untreated cataract samples. In treated cataract samples, lens tissue regenerated to fill the vacuoles. To identify the genes regulated by HAT inhibitors, qRT-PCR was performed on treated and untreated cataract samples to determine candidate genes. Expression of Acta1 and Stmn4, both of which are involved in the cytoskeleton, were altered significantly in C646+CPTH2 samples. Expression of Emd, a nuclear membrane protein, and Prtfdc1, which is involved in cancer cell proliferation, were altered significantly in CBP30+CPTH2 samples. Acta1, Acta2, Arrdc3, Hebp2, Hist2h2ab, Pmf1, Ppdpf, Rbm3, RGD1561694, Slc16a6, Slfn13, Tagln, Tgfb1i1, and Tuba1c in TH1834 samples were significantly altered. These genes were primarily related to regulation of cell proliferation, the cytoskeleton, and cell differentiation. Expression levels increased with the onset of cataracts and was suppressed in samples treated with HAT inhibitors.